Does FDI Bring Good Jobs to Host Countries? - Javorcik, Beata S. (World Bank, Washington, DC, 2014)
Are jobs created by foreign investors good jobs? The evidence reviewed in this article is consistent with the view that jobs created by FDI are good jobs, both from the worker's and the country's perspective. From the worker's perspective, this is because such jobs are likely to pay higher wages than jobs in domestic firms, at least in developing countries, and because foreign employers tend to offer more training than local firms do. From the country s perspective, jobs in foreign affiliates are good jobs because FDI inflows tend to increase the aggregate productivity of the host country.